Dispers Orange 13’ten çıkarak substitüe ftalosiyanin bileşiklerinin sentezi ve özelliklerinin tayini - Bozdoğan, Şida (My University, 2006)
DİSPERS ORANGE 13’TEN ÇIKARAK SUBSTİTÜE FTALOSİYANİN BİLEŞİKLERİNİN SENTEZİ VE ÖZELLİKLERİNİN TAYİNİ Ftalosiyaninler ilk kez 1907 yılında 2-siyanobenzamid’in hazırlanması sırasında saptandı. 1927 yılında piridin içinde bakır(I) siyanid ile 1,2-dibromobenzen’in ısıtılmasıyla % 23 verimle bakırlı ftalosiyanin sentezlendi. Substitue olmayan ftalosiyaninlerin yapıları Linstead’ın kapsamlı araştırmaları ve Robertson’un X-Ray difraksiyonu analizleri ile belirlendi. Ftalosiyaninler genellikle yüksek sıcaklıklarda sentezlenirler. Ftalosiyaninler ısıya, ışığa ve asitlere karşı dayanıklılıklarına rağmen düşük çözünürlüğe sahiptirler. Bu nedenle ftalosiyaninlerin çözünürlüğünü artırmak için çeşitli polar gruplar veya hacimli substitüentler kullanılmaktadır. Böylece farklı yapıda çözünür ftalosiyaninler sentezlenmektedir. Genellikle güçlü mavi yada yeşil olan renkleriyle ftalosiyaninler uzun yıllar boyu boyar madde olarak kullanılmışlardır. Ancak son yıllarda farklı substitüentlerle sentezlenen ftalosiyaninlerin ileri teknoloji alanlarında da kullanım alanına sahip olduğu görülmektedir. Ftalosiyaninler günümüzde, plastik ve metal yüzeylerin renklendirilmesi, fotokopi makineleri, kimyasal sensörler, fotodinamik kanser tedavisi gibi birçok alanda kullanılmaktadırlar. Yüksek Lisans Tez konum olan “Dispers Orange 13’ten Çıkarak Substitüe Ftalosiyanin Bileşiklerinin Sentezi Ve Özelliklerinin Tayini” kapsamında yeni simetrik ftalosiyanin bileşiklerinin sentezi ve yapılarının aydınlatılması hedeflenmiştir.

THE SYNTHESIS OF SUBSTITUED PHTHALOCYANINE COMPOUNDS STARTING FROM DISPERS ORANGE 13 AND CHARACTERIZATION OF THEIR PROPERTIES Phthalocyanines were obtained for the first time in 1907 as a by-product during the preparation of 2-cyanobenzamide. In 1927, PcCu was prepared in 23% yield by heating 1,2-dibromobenzene with copper(I) cyanide in pyridine. The structure of this unsubstituted phthalocyanine was determined by comprehensive researches of Linstead and X-Ray diffraction analyses of Robertson. Generally, phthalocyanines are obtained at high temperatures. Although phthalocyanines are resistant to heat, light and asid, they have less solubility. For this reason, various polar groups or bulky subtituents are used in synthesis of phthalocyanines for increasing solubility, so different kinds of soluble phthalocyanines can be obtained. Generally phthaocyanines that are strong blue or green were used as dyes. But in the recent years phthalocyanine that are obtained from different substituents have uses in new technological applications. These days phthalocyanines are used for many applications like making coloured metal and plastic surfaces, photocopy machine, chemical sensor, photodynamic cancer cure laser technology. In the thesis titled as “The Synthesis of Substitued Phthalocyanine Compounds Starting From Dispers Orange 13 and Characterization of Their Properties”, we have synthesized new symmetrical phthalocyanines and characterization of their structures. In this study, we have synthesized for the first time 4-(4-((E)-(4-((E)-benzyldiazenyl)napthalene-1-yl)diazenyl)phenoxy)phthalonitrile (4) , which is also soluble in some organic solvents like CHCl3, DMF, DMSO. And metal free and metal phthalocyanines were synthesized in suitable solvent and anhdrous metal salt ((Zn(OAc)2.2HO, CoCl2.6H2O). Because of products’ less solubility they were purificated by washing with different organic solvents. Uv/ Vis, FT-IR and 1H-NMR spectra confirm the proposed structure of the synthesized compounds.
Keywords: Kimya; Organik Kimya